2004
DOI: 10.1002/cne.20336
|View full text |Cite
|
Sign up to set email alerts
|

Projection and local interneurons in the sixth abdominal ganglion of the sand crab Emerita analoga (Hippidae)

Abstract: Hippid crabs are adapted for life in the surf zone of exposed sandy beaches, and their tailfan differs from the tailfans of other crustaceans with respect to morphology and motor control and in having nonspiking stretch receptors (NSR). To investigate how these crabs' mechanosensory systems are adapted to this turbulent environment, I used axonal back-filling and intracellular recording with dye-filled microelectrodes to describe afferent projections from the telson and morphologies and physiological responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…Our model assumptions are consistent with recently elucidated neurophysiological details of the motor system in E. analoga (Paul 2004). For example, there are bilaterally paired neurons in the uropod ganglion in E. analoga with properties similar to those in ganglia controlling rhythmic limb movement in crayfish (Hooper and DiCaprio 2004;Murchison et al 1993;Mulloney 1985a,b, 1986).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Our model assumptions are consistent with recently elucidated neurophysiological details of the motor system in E. analoga (Paul 2004). For example, there are bilaterally paired neurons in the uropod ganglion in E. analoga with properties similar to those in ganglia controlling rhythmic limb movement in crayfish (Hooper and DiCaprio 2004;Murchison et al 1993;Mulloney 1985a,b, 1986).…”
Section: Discussionsupporting
confidence: 62%
“…For example, there are bilaterally paired neurons in the uropod ganglion in E. analoga with properties similar to those in ganglia controlling rhythmic limb movement in crayfish (Hooper and DiCaprio 2004;Murchison et al 1993;Mulloney 1985a,b, 1986). There are also intersegmental projection neurons long enough to mediate the coupling between the uropod and fourth leg CPGs and potential coordinating interneurons similar to those in crayfish (Paul and Mulloney 1986;Paul 2004;Tschulum 2001).…”
Section: Discussionmentioning
confidence: 97%
“…6 A, C) [Letourneau, 1976;Paul et al, 1985]. The only gross anatomical evolutionary innovation has been the addition of a small sensory branch from motor nerve 6 (N6) in mole crabs that was previously designated N6sensory (N6s) based on the absence of somata in backfills [Paul et al, 1985;Paul, 2004]. We have confirmed that the N6s are sensory and determined that they innervate the bilaterally symmetric tufts of pappose setae on the anterior-dorsal face of the telson ( fig.…”
Section: Telson Sensory Nerves and Afferent Responses To Mechanical Ssupporting
confidence: 55%
“…quadrispina , and strongly skewed to more in the posterior cluster in E . analoga [Sigvardt et al, 1982;Paul, 2004;Bock and Paul, 2005;Bock, 2006]). These differences appear unrelated to either phylogeny or neurobehavioral differences, which was unexpected given the documented conservation of neural architecture across phylogeny in other arthropods [Buschbeck and Strausfeld, 1997;Buschbeck, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…mollusks that do not swim or flightless insects, are studied to see whether 'swim' or 'flight' neurons are present, suggesting whether the behavioral circuits have been lost or whether the absence of behavior is the prim-itive condition of a common ancestor [Arbas, 1983;Arbas et al, 1991;Rast and Braunig, 2001;Whiting et al, 2003;Katz and Newcomb, 2006]. Comparative neuroethological studies, at the level of identified neurons, have shown that similar neural circuits may underlie diverse behaviors, homologous neurons may play different behavioral roles in different animals, and that behavior can be lost in evolution [Arbas, 1983;Paul, 2004;Berkowitz, 2008;Katz, 2010]. Lost behavior can also be recovered, as seen in examples of stick insects where wings have been lost and regained [Whiting et al, 2003].…”
Section: Discussionmentioning
confidence: 99%